Validation of an air-liquid interface toxicological set-up using Cu, Pd and Ag well-characterized nanostructured aggregates and spheres - Svensson, Christian (Lund University, 2016)
Systems for studying the toxicity of metal aggregates on the airways are normally not suited for evaluating the effects of individual particle characteristics. This study validates a set-up for toxicological studies of metal aggregates using an air-liquid interface approach.

The set-up used a spark discharge generator capable of generating aerosol metal aggregate particles and sintered near spheres. The set-up also contained an exposure chamber, The Nano Aerosol Chamber for In Vitro Toxicity (NACIVT). The system facilitates on-line characterization capabilities of mass mobility, mass concentration and number size distribution to determine the exposure. By dilution, the desired exposure level was controlled.

Primary and cancerous airway cells were exposed to copper (Cu), palladium (Pd) and silver (Ag) aggregates. For Cu and Pd an exposure of sintered aerosol particles were also produced. The doses of the particles was expressed as particle numbers, masses and surface areas. For the Cu, Pd and Ag aerosol particles, a range of mass surface concentrations on the air-liquid interface of 0.4-10.7, 0.9-46.6 and 0.1-1.4 µg / cm2, respectively were achieved. Viability was measured by WST-1 assay, cytokines (Il-6, Il-8, TNF-a, MCP) by Luminex technology.

Statistically significant effects, and dose response, on cytokine expression was observed for SAEC cells after exposure to Cu, Pd or Ag particles. Also, a positive dose response was observed for SAEC viability after Cu exposure. For A549 cells, statistically significant effects on viability was observed after exposure to Cu and Pd particles.
The set-up produced a stable flow of aerosol particles with an exposure and dose expressed in terms of number, mass and surface area. Exposure related effects on the airway cellular models could be asserted.

Purpose:

The aim of this study is to validate a set-up for air-liquid interface toxicological research using highly characterized metal aggregate, and near spherical, aerosol particles. It combine a high output aerosol particle generator with continuous online exposure monitoring. The NACIVT was used for the study to ensure a high degree of deposition of aerosol particles on cell cultures, as well as to ensure a physiologically relevant environment during exposures.

Physical and biological data from air liquid interface cellular exposure studies.

system för att studera metall aggregerats toxiska effekter på luftvägarna är normalt sett inte anpassade för att utvärdera enstaka partikel egenskaper. Denna studien validerar ett system för sådana studier med hjälp av nano-strukturerade aerosol partiklar.

Systemet använde en gnistgenerator, kapabel att generera aggregerade och sfäriska aerosolpartiklar. En cell exponeringskammare, Nano Aerosol Chamber for In Vitro Toxicity (NACIVT), användes för exponering av celler. Aerosol partiklarna karaktäriserades med avseende på storlek och massa, antals, mass och ytarea-koncentration. Önskade exponeringsgrad ställdes in med hjälp av ett spädsystem.

Primära och standardiserade cancer celler blev exponerade för koppar, palladium och silver aerosol partiklar. Dosen uttrycktes i form av antal, massa och ytarea. För koppar, palladium och silver uppnåddes dosnivåer av 0.4-10.7, 0.9-46.6 och 0.1-1.4 µg / cm2. Viabilitet mättes med WST-1 teknik och cytokiner (Il-6, Il-8, TNF-a, MCP) med Luminex.

Statistiskt signifikanta effekter på cytokiner observerades för de primära cellerna efter exponering för koppar, palladium och silver. Dos respons kunde även säkerställas för viabilitet och koppar exponering. För standard celler kunde effekter säkerställas som ett resultat av koppar och palladium exponering.

Systemet validerades med avseende på dos och cellulära effekter som ett resultat av exponering i en air-liquid interface miljö.

Syfte:

Validering av ett system för air-liquid interface toxikologisk forskning med hjälp av väl karaktäriserade nano-strukturerade aerosol partiklar. Systemet kombinerar en aerosol partikel generator med hög output med on-line partikel karaktärisering. Cellexponeringskammaren NACIVT användes i systemet för att säkra en hög grad av partikel deponering på cellerna.

Fysiska och biologiska data från air liquid interface exponerings studier.
Validering av ett system för toxikologiska studier av aggregerade och sfäriska metall nanopartiklar - Validering av ett system för toxikologiska studier av aggregerade och sfäriska metall nanopartiklar
Keywords: Cytokinesis; Cytokines; toxicity; toxicitet; Nano-technology; Nanoteknik; Other Medical and Health Sciences; Annan medicin och hälsovetenskap